(untitled) (Homoeopathy for All, 2022)
The covid-19 pandemic initially started in Wuhan, China, and then swiftly spread all over the globe and on March 11, 2020, was declared as a pandemic.1Until now, Covid-19 has claimed more than 2.7 million lives worldwide.2 Since there is no pathognomical symptoms of Covid 19 at the initial stage, concluding its diagnosis is very difficult. Reported symptoms of Covid-19 are not limited to cough, fever, fatigue, sore throat, nasal obstruction, shortness of breath, headache, sputum production, and haemoptysis. Numbers of patients had also showed wider range of gastrointestinal symptoms such as diarrhoea, abdominal pain, low appetite, vomit, and many have shown renal and ocular symptoms.3Apart from the gastrointestinal symptoms many has reported variable complications in the eyes. Many patients suffer from post covid symptoms, which is called as long Covid. A retrospective, comparative study had been conducted to find out the manifestation of post Covid syndrome with 100 Covid-19 recovered patients throw some light examination, general examination including internal medicine and neurological evaluation done for the assessment. Study has shown that 5% had retinal vascular occlusion, 2% had anterior ischemic optic neuropathy AION, 3% had uveitis and 2% had central serous chorioretinopathy (CSCR).4,5 Homoeopathic remedies are reported to remove sequelae of long-lasting acute diseases. Moreover, homoeopathy has an extensive range of remedies to relieve complications of eyes. Hence it is possible that homoeopathy can be helpful to effectively manage the ocular manifestations of long Covid. In this article, we will be discussing the therapeutic indications of the possible remedies for long Covid with the help of repertorization.